Специфіка класифікації релігійно-паломницьких турів - Патійчук, Віктор Олексійович; Patiichuk, Viktor O. (Східноєвропейський національний університет імені Лесі Українки, 2015)
Узагальнено суть понять «релігійно-паломницький туризм»і «паломництво» й визначено співвідношення між цими науковими категоріями. Розглянуто методичні особливості проведення класифікації релігійно-паломницьких турів та вказано на специфіку таксономії основних видів і форм релігійного паломництва. Розкрито основні функції релігійно-паломницького туризму. Проаналізовано різноманітні наукові підходи до класифікації релігійно-паломницьких турів. Запропоновано авторську схему й принципи класифікації релігійного паломництва.

The essence of the concepts of «religious and pilgrimage tourism» and «pilgrimage» is overviewed and the relationship between these research categories is defined. There are methodical features of classification of religious pilgrimage tours in the article and the specificity of taxonomy of main types and forms of religious pilgrimage is given. The basic functions of religious and pilgrimage tourism are revealed. The variety of scientific approaches to classification of religious pilgrimage tours is analyzed. The author offered his own scheme and principles of religious pilgrimage classification.
The Specificity of Classification of Religious Pilgrimage Tours
Keywords: релігійно-паломницький туризм; паломник; класифікація; функції паломництва; релігійно-паломницький тур; pilgrim; classification; religious pilgrimage tour; religious and pilgrimage tourism